2020
DOI: 10.3390/antiox9111082
|View full text |Cite
|
Sign up to set email alerts
|

The Keap1/Nrf2 Signaling Pathway in the Thyroid—2020 Update

Abstract: The thyroid gland has a special relationship with oxidative stress. On the one hand, like all other tissues, it must defend itself against reactive oxygen species (ROS). On the other hand, unlike most other tissues, it must also produce reactive oxygen species in order to synthesize its hormones that contribute to the homeostasis of other tissues. The thyroid must therefore also rely on antioxidant defense systems to maintain its own homeostasis in the face of continuous self-exposure to ROS. One of the main e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
26
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 73 publications
0
26
0
7
Order By: Relevance
“…Therefore, investigations of the protective effects of Keap1/Nrf2 signaling that focus on specific tissues or organs are of great interest. Such studies have traditionally focused on tissues with detoxification functions such as the liver [ 6 , 7 ] but have also expanded to diverse tissues, including the kidney [ 8 , 9 ], skin [ 10 ], lung [ 11 ], colon [ 12 ], heart [ 13 ], nervous system [ 14 ], adipose tissue [ 15 ], pancreas [ 16 ] and thyroid [ 17 , 18 ], as evidenced by the respective tissue/organ-specific studies that are outlined below and comprise the majority of studies in the present Special Issue. Lastly, research on Nrf2 has expanded to encompass not only basic but also translational and clinical studies.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, investigations of the protective effects of Keap1/Nrf2 signaling that focus on specific tissues or organs are of great interest. Such studies have traditionally focused on tissues with detoxification functions such as the liver [ 6 , 7 ] but have also expanded to diverse tissues, including the kidney [ 8 , 9 ], skin [ 10 ], lung [ 11 ], colon [ 12 ], heart [ 13 ], nervous system [ 14 ], adipose tissue [ 15 ], pancreas [ 16 ] and thyroid [ 17 , 18 ], as evidenced by the respective tissue/organ-specific studies that are outlined below and comprise the majority of studies in the present Special Issue. Lastly, research on Nrf2 has expanded to encompass not only basic but also translational and clinical studies.…”
mentioning
confidence: 99%
“…Finally, the thyroid gland has a special relationship with oxidative stress because it must not only defend itself against reactive oxygen species but it must also actively produce them as part of the thyroid hormone synthesis process. In a review article from my group, Thanas et al discuss the latest studies on the roles of Keap1/Nrf2 signaling in the thyroid gland, which range from regulation of thyroid physiology to implication as a protective factor against diverse disease states including hypothyroidism, thyroid autoimmunity, thyroid enlargement (goiter), hyperthyroidism and thyroid carcinoma [ 18 ]. In addition, in an original research paper from my group, Chartoumpekis et al describe the global gene expression pattern in the thyroid of mice in response to excess iodide; by studying wild-type and Nrf2 knock-out mice in parallel, it is conclusively shown that Nrf2 is critical for mounting protective antioxidant, anti-inflammatory/anti-autoimmune and anti-fibrosis transcriptional responses in this setting [ 17 ].…”
mentioning
confidence: 99%
“…En Nepal, en una serie de pacientes adultos con IRC se detectaron variados casos de disfunción tiroidea: hipotiroidismo subclínico (27 %), hipotiroidismo clínico (8 %) e hipertiroidismo subclínico (3 %) (20) . La prevalencia de hipotiroidismo manifiesto en la población general oscila entre 0,2 % y 5,3 % en Europa y entre 0,3 % a 3,7 % de la población mundial (21) . Pero en los pacientes con IRC, hay una alta prevalencia de hipotiroidismo primario, muy correlacionada con la disminución de la tasa de filtración glomerular y el aumento del estrés oxidativo (21) .…”
Section: Discussionunclassified
“…La prevalencia de hipotiroidismo manifiesto en la población general oscila entre 0,2 % y 5,3 % en Europa y entre 0,3 % a 3,7 % de la población mundial (21) . Pero en los pacientes con IRC, hay una alta prevalencia de hipotiroidismo primario, muy correlacionada con la disminución de la tasa de filtración glomerular y el aumento del estrés oxidativo (21) . La deficiencia de vitamina D podría explicar este aumento de la frecuencia, aunque esta vitamina no fue medida en esta muestra.…”
Section: Discussionunclassified
See 1 more Smart Citation